Peran Kepemimpinan Dalam Mengakselerasi Penanganan Korupsi di Era Digitalisasi 5.0 Dan Sosial Media - Dwi Ajeng Maulidya Makalao; Harry Z Soeratin (Journal of Islamic Education Leadership, 2023)
The role of leadership in accelerating the handling of corruption in the era of digitalization 5.0 and social media. This research explores the role of leadership in addressing corruption in the era of digitalization 5.0 and social media and discusses the challenges and potential solutions. The objective of the research is to understand the role of leadership in addressing corruption in the era of digitalization 5.0 and social media and to discuss the challenges and potential solutions. The research methods used are a qualitative descriptive analytical document study to explain the situation being studied and document or text analysis to assess the readability of texts related to the topic. Key findings are not presented in the text. The significance of the research is to provide insights into how effective and integrity-based leadership, as well as collaborative and inclusive leadership, can help address corruption in the era of digitalization 5.0 and social media